Situation Report: Czechoslovakia, 9 August 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Economic Results, January-June 1972 Guidelines for the 1973 Plan Soviet Success at Karlovy Vary Film Festival Jehovah's Witnesses under Pressure